The Effect of Work Discipline and Reward Punishment on Employee Performance of the Tulang Bawang Regency Agriculture Office - Ratikaningsih, Sisda; Josiah, Trisnowati (Saburai International Journal of Social Sciences and Development, 2024)
Work discipline at the Tulang Bawang Regency Agriculture Office is essential for employee performance and optimal service quality. But discipline levels remain low, with many employees often late or absent without a clear reason at more than 5%. This hampers the objectives of the work program. Due to budget and regulatory constraints, rewards and punishments have not been formally used. As a result, many employees have become unmotivated, resulting in decreased performance and productivity. The agency is submitting a proposal to the local government for better policies to improve employee performance. Using a quantitative descriptive approach, this research was conducted at the Agriculture Office of Tulang Bawang Regency. The purpose of this study was to provide a systematic and honest description of work discipline and penalty punishment systems, and how these impact on employee performance. This study involved all 85 employees of the agency, so the sample was almost the same as all employees, namely 84 people. The dependent variable, employee performance (Y), is expected to be influenced by the independent variables (X1) and payment penalty (X2). The results of data analysis and hypothesis testing show that Work Discipline (X1) affects employee performance (Y) at the Tulang Bawang Regency Agriculture Office by 59.9 percent. Punishment Punishment (X2) affects employee performance by 61.9 percent simultaneously, and Work Discipline (X1) affects employee performance by 51.2 percent. Other factors affect 48.8 percent of the total.